Travel Demand, Transport Systems and Regional Development: Models in Co-ordinated Planning - Engström, Mats-G.; Sahlberg, Bengt (Lund : Royal University of Lund, Dept. of Geography, 1973)
This study covers studies of the country (Sweden) as a whole as well as detailed studies of separate regions, organizations, functions and transport systems.
Includes bibliographical references.
ne 27/02/2018
Loan
Keywords: Transportation; Regional Planning